Biochemical and ultrastructural indices of muscle damage after a twenty-one kilometre run - Goodman, C.; Henry, G.; Dawson, B.; Gillam, I.; Beilby, J.; Ching, S.; Fabian, V.; Dasig, D.; Kakulas, B.; Morling, P. (Australian Journal of Science and Medicine in Sport, 1998)
Increased serum concentrations of intracellular proteins are generally accepted as good indicators of muscle damage. The mechanism of this damage is, however, poorly understood. Twenty male runners completed a 21 km run in as fast a time as possible. Blood samples were obtained from each subject just prior to, immediately after, and 24 hr after the run. Samples were analysed for haemoglobin, haematocrit, creatine kinase (CK), myoglobin (Mb) and malondialdehyde (MDA) concentrations and corrected for percentage change in plasma volume (PV). Percutaneous muscle biopsies were taken from the lateral gastrocnemius muscle of 6 of the subjects 24 hr before and 24 hr after the run and examined by electron microscopy. Mb levels in the serum increased significantly (p < 0.001) immediately post-exercise, while CK levels increased significantly (p < 0.001) at 24 hours post-exercise. The PV corrected serum MDA levels were very close (p = 0.06) to a significant increase immediately post-exercise. Ultrastructural examination of pre-exercise samples revealed evidence of muscle changes consistent with endurance exercise training, but no further damage was evident at 24 hr post-exercise. It is thus suggested that the increased serum levels of CK and Mb after the 21 km run may be a result of free radical induced cell membrane damage and increased permeability, as evidenced by elevated serum MDA levels, and not due to mechanical muscle damage.